PENGARUH SOSIALISASI PERPAJAKAN, PENGETAHUAN PERPAJAKAN, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KESADARAN WAJIB PAJAK SEBAGAI VARIABEL INTERVENING (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA PEKANBARU SENAPELAN) - Tuti Wulandari; Andreas -; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research are to analyze the influence of taxpayer socialization, taxpayer knowledge, and quality of service to taxpayer compliance, directly or indirectly, by usingtaxpayer awareness as an intervening variable.The sample of this research from of 100 correspondences who are as taxpayers listed in KPP Pratama Pekanbaru Senapelan.The method of sampling using convenience sampling. The data were analysed using the path analysis with SPSS version 19.0. The results of the research showed that the tax socialization did have effect to the tax awareness. Secondly, the tax knowledge did have effect to the tax awareness. Third, quality of service did have effect to the tax awareness.Fourth, the tax socialization did have effect tothe tax compliance. Fifth, the tax knowledge did have effect tothe tax compliance. Sixth, quality of service did have noteffect tothe tax compliance. Seventh, the tax awareness did have effect tothe tax compliance. Eighth, the tax awareness incapable as an intervening variable tax socialization to tax compliance. Ninth, the tax awareness incapable as an intervening variable tax knowledge to tax compliance. Tenth, the tax awareness able as an intervening variable quality of service to tax compliance.Keywords: Taxpayer Socialization ,Taxpayer Knowledge, Quality of Service, Taxpayer Awareness, and Taxpayer Compliance